THE VOA SLOVENIAN SERVICE IN THE 1970S BETWEEN BUDGET CUTS, CONGRESS, AND DIASPORIC LANGUAGE VITALITY: “WHEN THE VOICE OF AMERICA FELL SILENT IN SLOVENIAN” - Hazemali, David; Klemenčič, Matjaž (Slavia Centralis, 2026)
This article analyzes the cancellation and restoration of Voice of America (VOA) Slovenian-language broadcasts in 1974–1976 as a case in which an administrative decision transforms into a broader question of the public presence of a “small language.” In February 1975, the United States Information Agency (USIA) terminated the daily half-hour broadcast in Slovenian for budgetary reasons–the only language service entirely eliminated at that time. The cancellation mobilized the Slovenian-American community, which articulated its protest through ethnic fraternal organizations, the press, and political connections. Key roles were played by former U.S. Senator of Slovenian descent Frank J. Lausche, political émigré and Georgetown University Professor Dr. Ciril Žebot, and VOA Slovenian Service editor Konrad Peter Mejač. Legislative action in the U.S. Congress led to the passage of a law in April 1976 that mandated the restoration of broadcasts and represented the first U.S. legislation containing an explicit provision regarding Slovenia. The case illuminates the dynamics among federal administration, congressional oversight, and the Slovenian-American community in maintaining “minor languages” within the institutional frameworks of major states.